Effect Of Fermentation Duration Of Diaper-Based Liquid Organic Fertilizer On Nitrogen (N) And Potassium (K) Content - Dania Oktafia, Dhiya; Sulistio, Irwan; Suryono, Hadi; Marlik, Marlik; Margono, Margono (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2025)
The increasing birth rate and number of toddlers each year have led to a rise in diaper usage, resulting in significant diaper waste. Improper management of this waste can cause environmental problems. One potential solution is utilizing diapers as raw material for liquid organic fertilizer production. This study aimed to determine the differences in bacterial starter addition and fermentation duration of liquid organic fertilizer from diapers in terms of nitrogen and potassium content. A quasi-experimental design with a post-test only control group was applied. The study focused on the hydrogel in the diaper’s inner layer. The independent variable was fermentation duration (12, 15, 18, and 21 days), while the dependent variables were nitrogen and potassium content, each with six replications. Data were analyzed using One Way ANOVA. Results showed average nitrogen content for fermentation durations of 12 days (0.34%), 15 days (0.43%), 18 days (0.53%), and 21 days (0.64%). The lowest nitrogen content was found at 12 days (0.32%), and the highest at 21 days (0.66%). Average potassium content for fermentation durations was 12 days (0.27%), 15 days (0.36%), 18 days (0.43%), and 21 days (0.54%). The lowest potassium content occurred at 12 days (0.25%), and the highest at 21 days (0.56%). In conclusion, there were significant differences in nitrogen and potassium content across fermentation durations. Further studies are recommended to optimize bacterial starter acclimatization, monitor temperature and pH, and apply sampling techniques according to national standards (SNI).